ANALYSIS OF DISASTER MITIGATION STRATEGY IN THE FIRE EVENT OF THE PRODUCTION PART IN PT X - Margaretha Iandri; Bina Kurniawan; Baju Widjasena (Jurnal Kesehatan Masyarakat, 2019)
PT X is a company that manufactures rubber, which carries the risk of fire hazard and must have a building protection component and procedures from fire hazards that meet K3 requirements. Some of the fire prone points are fogging, chemical storage. In 2015 PT X was recorded as having experienced a fire in the fumigation section due to negligence of workers and negligence of work supervision. This study aims to analyze how the implementation of disaster mitigation strategies implemented by PT X related to pre-disaster stages. This type of research is a qualitative descriptive that describes and analyzes objects according to the conditions of the study. The subjects of this study were divided into two main informants and triangulation who held positions as leaders in the company as well as security guards and foremen involved in the company's emergency response team. This research refers to the Disaster Mitigation Strategy issued by the Domestic Government. The results of this study indicate that the management and PT X emergency response team have not implemented a disaster mitigation strategy which includes mitigation mapping, mitigation monitoring, information dissemination and fire training. Especially in the SOP section on emergency response, evacuation route maps, information dissemination related to safety induction.